Unearthing the diversity of Japanese Magelona (Annelida: Magelonidae); three species new to science, and a redescription of Magelona japonica - Taylor, Abbie; Mortimer, Kate; Jimi, Naoto (Zootaxa, 2022)
Whilst seven species of magelonids have been originally described from the North-Western Pacific Ocean, only two have been from Japanese waters. Given the often high diversity of magelonid species within relatively small regions, the number of Japanese Magelona species is likely to be higher. The validity of several recorded species from the region has been additionally called into question, and the urgent need for a review of magelonids of Japan highlighted. Newly collected samples of magelonids have emphasised the presence of three species new to science occurring off Japan, herein described: Magelona alba sp. nov., Magelona armatis sp. nov., and Magelona boninensis sp. nov. A redescription of Magelona japonica is additionally provided, along with notes on a fifth species, which approaches Magelona cornuta. A dichotomous identification key to magelonid species of the North-Western Pacific Ocean, along with a table of characters for all five observed species is provided.